Powerful switch based on CX1525A thyratron - Chertishev, I.A.; Ivakhnenko, M.V.; Kaplij, D.A.; Khomyakov, E.A.; Kosoi, A.I.; Titov, V.Yu.; Tur, Yu.D.; Tsymbal, V.A.; Zajtsev, E.I.; Zajtsev, I.N. (Вопросы атомной науки и техники, 2014)
Thyratrons of obsolete types TGI1-2500/50, TGI1-2500/35, TGI1-5000/50 are used in modulators of NSC KIPT of as a switch, their service life has expired. To update the modulator we selected thyratron СХ1525А of company EЕV, which technical parameters met the requirements: switched current 2.3 kA, anode voltage up to 40 kV, pulse frequency up to 300 Hz, pulse duration 5 μs. Thyratron switchboard based on СХ1525А was de-signed and constructed. The results of study the switch operation in mode of active accelerator are reported. В модуляторах ННЦ ХФТИ в качестве коммутатора используются тиратроны типа ТГИ1-2500/50, ТГИ1-2500/35, ТГИ1-5000/50, ресурс которых исчерпан. Для модификации модулятора выбран тиратрон СХ1525А производства фирмы EЕV, по техническим характеристикам удовлетворяющий параметрам: коммутируемый ток 2,3 кA; анодное напряжение до 40 кВ; частота посылок до 300 Гц; длительность импульса 5 мкс. Проведена разработка и изготовление тиратронной стойки на основе СХ1525А. Приведены результаты исследования работы коммутатора в режиме действующего ускорителя. У модуляторах ННЦ ХФТІ в якості комутатора використовуються тиратрони типу ТГІ1-2500/50, ТГІ1-2500/35, ТГИ1-5000/50, ресурс яких було вичерпано. Для модифікації модулятора було вибрано тиратрон СХ1525А виробництва фірми ЕЕV, який по технічним характеристикам відповідає параметрам: комутуємий струм 2,3 кА; анодна напруга до 40 кВ; частота посилок до 300 Гц, тривалість імпульсу 5 мкс. Проведена розробка та виготовлення тиратронної стойки на основі СХ1525А. Приведено результати дослідження роботи комутатора в режимі діючого прискорювача.